2020
DOI: 10.3389/fpls.2020.00429
|View full text |Cite
|
Sign up to set email alerts
|

A Soybean Deletion Mutant That Moderates the Repression of Flowering by Cool Temperatures

Abstract: Ambient growing temperature and photoperiod are major environmental stimuli that summer annual crops use to adjust their reproductive phenology so as to maximize yield. Variation in flowering time among soybean (Glycine max) cultivars results mainly from allelic diversity at loci that control photoperiod sensitivity and FLOWERING LOCUS T (FT) orthologs. However, variation in the thermal regulation of flowering and its underlying mechanisms are poorly understood. In this study, we identified a novel mutant (ef1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Up-regulation of GmCOL5a/5b and GmCOL6a/6b under high-temperature conditions ( Figure 3 and Figure 4 ) indicated that their expressions showed a positive relationship with the expressions of GmFT2a and GmFT5a , which further suggests that these GmCOLs are involved in high-temperature response. Recently, Zhang et al (2020) reported that cool temperature (18 °C) delays flowering and up-regulates GmCOL2b expression at the fourth trifoliate leaf (V4) stage [ 59 ], suggesting that GmCOL2b works as a flowering repressor upon cool ambient temperatures. However, GmCOL1a/1b and GmCOL2a/2b , which are the best-known GmCOL genes in soybean plants, were, unexpectedly, not changed in response to high temperature ( Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of GmCOL5a/5b and GmCOL6a/6b under high-temperature conditions ( Figure 3 and Figure 4 ) indicated that their expressions showed a positive relationship with the expressions of GmFT2a and GmFT5a , which further suggests that these GmCOLs are involved in high-temperature response. Recently, Zhang et al (2020) reported that cool temperature (18 °C) delays flowering and up-regulates GmCOL2b expression at the fourth trifoliate leaf (V4) stage [ 59 ], suggesting that GmCOL2b works as a flowering repressor upon cool ambient temperatures. However, GmCOL1a/1b and GmCOL2a/2b , which are the best-known GmCOL genes in soybean plants, were, unexpectedly, not changed in response to high temperature ( Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the downregulation of COL1a/b by RNAi resulted in the downregulation of E1 (Wu et al, 2019). Furthermore, E1 and E1Lb were induced by chilling at 18°C in LD, but such induction was not observed in an early‐flowering mutant in which a 214 kb segment containing COL2b was deleted (Zhang et al, 2020b). These findings suggest that soybean COL genes could function as activators of E1 expression, an interesting hypothesis to be addressed in the future.…”
Section: E1 Is a Central Hub In The Photoperiodic Flowering Mechanism In Soybeanmentioning
confidence: 99%
“…57 There is even an indication that E1 expression may be weakly promoted by GmCOL2b. 54 We favor a hypothesis in which PvCOL2 and PvE1 act in parallel, and to some extent redundantly, to repress multiple FT genes (Figure 4D). However, the identification of functional variants for PvE1 and PvCOL1 and comprehensive functional analysis of E1-like and group Ia COL genes in soybean will be needed to clarify these relationships and how they may differ between the two species.…”
Section: Discussionmentioning
confidence: 78%
“…17,18 In soybean, the closest SD comparator of common bean, weak early-flowering phenotypes of COL1b missense and COL2b deletion mutants indicate a modest repressive role for both genes under LD. 53,54 The markedly stronger effect of mutations in the single common bean COL2 gene could simply reflect the lower degree of redundancy relative to the paleotetraploid soybean but may also indicate that COL2 has a more critical functional role in bean than in soybean. Nevertheless, the fact that col2 genotypes are only partially insensitive to photoperiod indicates that other genes also contribute to repression of flowering under LD.…”
Section: Discussionmentioning
confidence: 99%